(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to examine the impact of evangelist marketing on enhancing brand personality and its dimensions as perceived by online shoppers in the capital city of Baghdad, amid the growing reliance on unpaid recommendations in digital environments. To achieve this objective, an electronic questionnaire was distributed to collect data related to the study variables, resulting in 421 valid responses. The data were analyzed using various statistical techniques, including percentages, means, standard deviations, and reliability coefficients (Cronbach’s Alpha and McDonald’s Omega), along with confirmatory factor analysis (CFA) to verify construct validity and simple linear regression to test the hypotheses. The findings indicate that evangelist marketing strongly influences customers’ perceptions of brand personality, highlighting the significant role of digital social interaction in shaping brand-related mental representations. Moreover, the results suggest that the approach of evangelist marketing contributes to shaping customers’ impressions of the brand’s sincerity and its concern for customer satisfaction, which in turn fosters a sense of trust and reliance on the brand.